THE ROLE OF INTERNATIONAL TRADE ORGANIZATIONS IN ENHANCING COOPERATION AND FREE TRADE BETWEEN COUNTRIES - Loso Judijanto; Sari Mariahma Nova Sipayung (Adisam Publisher, 2025)
The International Trade Organization (ITO) plays a crucial role in enhancing economic cooperation and strengthening free trade between countries. Organizations such as the World Trade Organization (WTO), the International Monetary Fund (IMF), and the World Bank act as facilitators in creating fair and transparent trade policies. The ITO plays a role in reducing trade barriers, such as tariffs and quotas, and resolving trade disputes that can hamper global economic growth. In addition, this organization also helps developing countries increase their trade capacity through technical and financial assistance. With the role of the ITO, countries can more easily access international markets, increase product competitiveness, and strengthen global economic stability. Therefore, cooperation in the ITO is the main key to realizing sustainable and equitable free trade for all parties.